An Analysis upon Life Experiences and Association among Husbands’ Migration and Left behind Wives’: A Case Study of Rural India: Exploring the Impact of Husband's Migration on Women's Autonomy and Labor Force Participation: A Study in Rural India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper examines the impact of husband’s migration on lives of women left behind. We focus on two dimensions of women’s lives: (a) Women’s autonomy and control over their lives; (b) Women’s labor force participation. Results suggest that household structure forms the key mediating factor through which husband’s absence affects women. Women not residing in extended families are faced with both higher levels of responsibilities as well as greater autonomy, while women who live in extended households do not experience these demands or benefits.Research emphasizing effects of migration on left behind families often focus on implications of absent fathers, particularly in rural India and areas with historic male migration. Yet, information on the experiences of left behind wives in a patriarchal and familial setting is scanty. This Study explore the socio-cultural challenges facing wives of migrants, in rural India. Specifically it examines the stigmatized experiences and the effect of cultural constrains on women adjustment to life in the absence of their husbands.